2021
DOI: 10.1002/jsfa.11307
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur fertility management to enhance methionine and cysteine in soybeans

Abstract: BACKGROUND: Soybeans (Glycine max) are a major protein source both for humans and non-ruminant livestock; however, the usability of soybean protein is limited by the concentration of the essential sulfur (S)-containing amino acids methionine and cysteine (MET+CYS). Traditional efforts to improve protein quality in soybeans have largely been focused on plant breeding but soil S fertility may also influence seed MET+CYS concentration. Crop S deficiencies are increasingly common due to soil depletion by high yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Albumin and globulin proteins account for ca. 70% of the soybean seed’s proteome. , Although similar biosynthesis trends have been previously observed, , most of these studies have focused on assessing the seed’s total protein content or the storage proteins on mature seeds as a function of different agricultural traits. , Therefore, a precise profile of storage proteins biosynthesis throughout the seed development was poorly explored. The results presented herein confirm that the storage protein accumulation escalates during the cell elongation phases, i.e., in the aftermath of the cease in cell division and differentiation taking place up to the R 5.5 developmental stages (Figure ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Albumin and globulin proteins account for ca. 70% of the soybean seed’s proteome. , Although similar biosynthesis trends have been previously observed, , most of these studies have focused on assessing the seed’s total protein content or the storage proteins on mature seeds as a function of different agricultural traits. , Therefore, a precise profile of storage proteins biosynthesis throughout the seed development was poorly explored. The results presented herein confirm that the storage protein accumulation escalates during the cell elongation phases, i.e., in the aftermath of the cease in cell division and differentiation taking place up to the R 5.5 developmental stages (Figure ).…”
Section: Resultsmentioning
confidence: 84%
“…Given that S, alongside playing essential roles in plant metabolism, also encompasses both cysteine and methionine sulfur-amino acid residues in the primary structure of glycinin, these results present resounding evidence that the strong correlations observed between the storage proteins and sulfur concentration throughout soybean seed development (Figure a,b) are indeed related to sulfur’s important role as the building blocks of the glycinin amino acid residue backbone. This is supported by agricultural trials where soil and foliar sulfur fertilization have been reported to change the profile of storage proteins and increase the total protein content in soybean seeds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, new cultivars with high SAA contents have not been reported, although several QTLs and candidate alleles associated with amino acid contents have been found (Panthee et al, 2006;Ramamurthy et al, 2014). S (MgSO 4 ) application increased the proportion of Met + Cys in soybean seeds (Rushovich and WeilSulfur, 2021), and this required the correct application of S, which might be complex. Moreover, materials with high sulfurcontaining amino acids have been influenced by environmental factors, nitrogen sources, and the availability of reduced forms of sulfur, which limits their use in field production.…”
Section: Discussionmentioning
confidence: 99%
“…Animal protein is rich in a variety of essential amino acids, but also rich in fat and cholesterol, leading to a high incidence of various chronic diseases [ 2 ]. Additionally, soy protein does not contain cholesterol, and the contents of methionine and branched-chain amino acids (BCAAs) are low compared with animal proteins [ 3 , 4 ]. Although leucine or its metabolite β-hydroxy-β-methylbutyric acid can improve muscle function [ 5 ], aberrant metabolism of BCAAs and high circulating concentrations of BCAAs are a hallmark of metabolic disorders, including obesity, insulin resistance and type 2 diabetes mellitus, cancer, and heart failure [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%